OXYGEN CONSUMPTION IN RELATION TO SPONTANEOUS ACTIVITY AND AMBIENT OXYGEN IN FIVE MARINE TELEOSTS - Hamsa, K M S Ameer; Kutty, M N (Indian Journal of Fisheries, 2011)
Some metabolic adaptations of 5 species of South Indian marine teleosts,onamely Caranx carangus (Bloch), Chorintmus lysan (Forskal), Chanos chanoso(Forskal), Synagris furcosus (Day) and Gerres lucidus (Day) were studied.The fishes were acclimated to and tested at an average temperature of 30Â°C and357^^ salinity